Erosion of the healthy soldier effect in veterans of US military service in Iraq and Afghanistan - Bollinger, Mary J (Popul Health Metr, 2015)
BACKGROUND: This research explores the healthy soldier effect (HSE) – a lower mortality risk among veterans relative to the general population—in United States (US) veterans deployed in support of operations in Iraq and Afghanistan (OEF/OIF/OND). While a HSE has been affirmed in other OEF/OIF/OND populations, US veterans of OEF/OIF/OND have not been systematically studied. METHODS: Using US Department of Veterans Affairs (VA) administrative data, we identified veterans who (1) had been deployed in support of OEF/OIF/OND between 2002 and 2011 and (2) were enrolled in the VA health care system. We divided the VA population into VA health care utilizers and non-utilizers. We obtained Department of Defense (DOD) administrative data on the OEF/OIF/OND population and obtained VA and DOD mortality data excluding combat deaths from the analyses. Indirect standardization was used to compare VA and DOD cohorts to the US population using total population at risk to compute the Standardized Mortality Ratio (SMR). A directly standardized relative risk (DSRR) was calculated to enable comparisons between cohorts. To compare VA enrollee mortality on military specific characteristics, we used a DOD population standard. RESULTS: The overall VA SMR of 2.8 (95% Confidence Interval [CI] 2.8-2.9), VA utilizer SMR of 3.2 (95% CI 3.1-3.3), VA non-utilizer SMR of 0.9 (95% CI 0.8-1.1), and DOD SMR of 1.5 (95% CI 1.4-1.5) provide no evidence of a HSE in any cohort relative to the US standard population. Relative to DOD, both the total VA population SMR of 2.1 (95% CI 2.0-2.2) and the SMR for VA utilizers of 2.3 (95% CI 2.3-2.4) indicate mortality twice what would be expected given DOD mortality rates. In contrast, the VA enrollees who had not used clinical services had 40% lower than expected mortality relative to DOD. CONCLUSIONS: No support was found for the HSE among US veterans of OEF/OIF/OND. These findings may be attributable to a number of factors including post-deployment risk-taking behavior, an abbreviated follow up period, and the nature of the OEF/OIF/OND conflict.